(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Pseudomonas aeruginosa (P. aeruginosa) is an opportunistic microorganism that requires damaged mucus membranes and epithelial tissues to cause acute infections. It had been stated that P. aeruginosa alters mammalian cytokinesis in a type III secretion system and exotoxin T (ExoT)-related way. Objective: To identify exoT gene local isolates of P. aeruginosa isolated from burn infections. Methods: Forty bacterial isolates of P. aeruginosa (isolated from burn infection) were identified by standard laboratory methods and polymerase chain reaction (PCR) technique was applied for the detection of the gene encoding for ExoT. Results: The results showed that PCR amplification of exo T gene occurred in 24 (60 %) isolates out of the enrolled 40 isolates of P. aeruginosa while 16 (40 %) of the isolates showed negative amplification reactions. Conclusion: It appeared that exoT can be a significant virulence factor expressed by 60 % of P. aeruginosa isolates as indicated by positive PCR-amplification results. Keywords: Burn infections, Exotoxin T, type III secretion system, PCR, P. aeruginosa Citation: Hanoon RA, Auda IG, Aziz IH. Detection of ExoT gene in local isolates of Pseudomonas auroginosa in a sample of burn infection. Iraqi JMS. 2017; Vol. 15(4): 358-363. doi: 10.22578/IJMS.15.4.6